Depression and Insomnia in Patients on Maintenance Hemodialysis - Uzzal, Obaidul Kadir; Islam, Md Nazrul; Ahmed, Parvez Iftekhar; Mamun, Md Abdullah Al; Hossain, Mohammad Bellal; Bhuiyan, Ferdous Kamal; Khan, Md Firoz (Journal of Dhaka Medical College, 2016)
Depression and sleep disorders are more frequent in patients on maintenance hemodialysis (HD) than the general population, and are associated with reduced quality of life and increased mortality risk. The purpose of this study was to assess the prevalence of depression and insomnia in patients on HD and to correlate these with the demographic and biochemical profile. A cross sectional study was conducted among 316 patients on maintenance HD for more than 3 months. There was high prevalence of depression (92.7%) and insomnia (91.1%), Depression was significantly more in patients with urban population (P=0.007), unemployed patients (P=0.007), who had less income.(P=0.018) who got dialysis >12 months (P=0.009) and who got dialysis 2 session per week (P value=0.014). Insomnia was found significantly more in female (P=0.018) and among thosepatients of less income group (P=0.008) and in patients who got at least two sessions of hemodialysis per week (P=0.011).Low serum hemoglobin isassociated with both depression and insomnia (P<0.5), while low serum albumin concentration is found associated with depression (P<0.5). J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 3-11